Forensic evaluation of persons with destructive behavior in the postwar Bosnia and Herzegovina - Novaković Milan; Čabarkapa Milanko; Ille Tanja; Ilanković Andrej (Vojnosanitetski Pregled)
Background/Aim. Different persons show forensic differences related to aggressive behavior in criminal and violation acts. The aim of this study was to forensically analyze the influence of socio-dynamic conditions and stress in testing the forensic hypothesis of hetero-destruction, and analysis of persons with destructive behavior in Bosnia and Herzegovina (B&H) in the period from 1996−2005. Methods. The experimental group consisted of 125 persons who had committed a crime according to the Criminal Law of B&H and, thus were under security measures or treatment. The control group consisted of 125 persons who had committed a violation. The following psychometric tests/questionnaires were used in the study: Eysenek Personality Questionnaire (EPQ), Beck Anxiety Inventory (BAI) and Profile Index of Emotions (PIE). Results. There were a significant difference between the respondents’ groups related to gender (p < 0.01), while broken family, migration, and family comorbidity showed insignificant differences. EPQ test showed statistically significant differences between the groups for all four variables, and Beck test found significant differences only for some ones. PIE test proved the relations of the basic emotions confirmed by discriminative function. Conclusion. High level of hetero-destruction in crime was proven in the study. Criminal acts and violations were committed by the persons without psychopathology, as well as by the persons with mental diseases, which rendered a forensic responsibility and analysis of such an influence on behavior.